Tributyl and Triphenyl Substituted Tin Derivative of N-(o-Hydroxy Substituted Benzyl) Alamines - Gangwar, Tripti; Shah, Ranjana; Chandra, Madhup (Asian Journal of Chemistry, 2010)
Several tributyl and triphenyl substituted tin derivatives of N(o-hydroxy substituted benzyl) alanines have been prepared by the interaction of tributyltin or triphenyltin triisopropoxide with the latter employing alcoholysis reactions in 1 : 1 and 2 : 1 stoichiometric ratios in benzene or toluence as the reaction medium. The compounds were obtained as dark viscous liquids in case of tributyltin derivatives and as coloured solids in case of triphenyltin derivatives. All these compounds were characterized by elemental and azeotrope analyses, as well as by IR and PMR spectral measurements.